The Divergence of the Influence of Ulama and Dayah in the Dynamics of Electoral Politics in East Aceh Regency - Rahma, Alya; Rizwan, M; Muzaffarsyah, Teuku; Faisal, Naidi; Sarifa, Sarifa (JUSS (Jurnal Sosial Soedirman), 2024)
This research discusses the dlvergence of influence of ulama and dayah in electoral politics in East Aceh Regency. Use of electoral political theory (elections), using qualitative research methods. Findings from the results of research in the fileld regarding "Divergence of influence of ulama and dayah in the electoral political constellation in East Aceh Regelcy", can be concluded that: 1) The divergence of political influence that ulama and dayah have in the implementation of the electoral political constellation is very large, many people folllow or make ulama as a reference in determining their choice of politilal partiles in the general election in East Aceh Regency. 2) In providing support to political parties or election participants, ulama and dayah have causes or driving factors that cause divergence in poliltical support from ulama and dayah towards political parties in the implementation of elelctoral politilcs in East Aceh Regency.